Acoustic input and efferent activity regulate the expression of molecules involved in cochlear micromechanics - Lamas, Verónica; Arevalo, Juan C.; Juíz, José M.; Merchán, Miguel A. (Frontiers in Systems Neuroscience, 2015)
Electromotile activity in auditory outer hair cells (OHCs) is essential for sound amplification. It relies on the highly specialized membrane motor protein prestin, and its interactions with the cytoskeleton. It is believed that the expression of prestin and related molecules involved in OHC electromotility may be dynamically regulated by signals from the acoustic environment. However little is known about the nature of such signals and how they affect the expression of molecules involved in electromotility in OHCs. We show evidence that prestin oligomerization is regulated, both at short and relatively long term, by acoustic input and descending efferent activity originating in the cortex, likely acting in concert. Unilateral removal of the middle ear ossicular chain reduces levels of trimeric prestin, particularly in the cochlea from the side of the lesion, whereas monomeric and dimeric forms are maintained or even increased in particular in the contralateral side, as shown in Western blots. Unilateral removal of the auditory cortex (AC), which likely causes an imbalance in descending efferent activity on the cochlea, also reduces levels of trimeric and tetrameric forms of prestin in the side ipsilateral to the lesion, whereas in the contralateral side prestin remains unaffected, or even increased in the case of trimeric and tetrameric forms. As far as efferent inputs are concerned, unilateral ablation of the AC up-regulates the expression of α10 nAChR transcripts in the cochlea. Limited, unbalanced efferent activity after unilateral AC removal, also affects prestin and β-actin mRNA levels. These findings support that the concerted action of acoustic and efferent inputs to the cochlea is needed to regulate the expression of major molecules involved in OHC electromotility, both at the transcriptional and posttranscriptional levels.